2023
DOI: 10.1097/hc9.0000000000000012
|View full text |Cite
|
Sign up to set email alerts
|

Validation of risk scores for allograft failure after liver transplantation in Germany: a retrospective cohort analysis

Abstract: A growing number of clinical risk scores have been proposed to predict allograft failure after liver transplantation. However, validation of currently available scores in the Eurotransplant region is still lacking. We aimed to analyze all clinically relevant donor and recipient risk scores on a large German liver transplantation data set and performed a retrospective cohort analysis of liver transplantations performed at the Charité—Universitätsmedizin Berlin from January 2007 until December 2021 with organs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…30,40 However, MEAF was chosen as a primary outcome measure for this study as it is a previously well-validated surrogate of early allograft function independently associated with the strongest clinical end-pointtransplant survival. [41][42][43] Importantly, MEAF was a significant predictor of both severe morbidity and mortality in all the patients included in the present study. Although the level of significance was not reached in the dHOPE group, the ORs for the association between MEAF and the development of severe complications were consistent in both arms.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…30,40 However, MEAF was chosen as a primary outcome measure for this study as it is a previously well-validated surrogate of early allograft function independently associated with the strongest clinical end-pointtransplant survival. [41][42][43] Importantly, MEAF was a significant predictor of both severe morbidity and mortality in all the patients included in the present study. Although the level of significance was not reached in the dHOPE group, the ORs for the association between MEAF and the development of severe complications were consistent in both arms.…”
Section: Discussionmentioning
confidence: 56%
“…The choice of primary outcome measure based on laboratory findings in machine perfusion trials is being widely criticized for unknown clinical relevance 30,40 . However, MEAF was chosen as a primary outcome measure for this study as it is a previously well-validated surrogate of early allograft function independently associated with the strongest clinical end-point – transplant survival 41–43 . Importantly, MEAF was a significant predictor of both severe morbidity and mortality in all the patients included in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…As a result, donor age is less important than before. In addition, the inclusion of other variables and indexes in the model may reduce the effect of donor age, which is not present in our study 46 48 .…”
Section: Discussionmentioning
confidence: 72%
“… 10 This study found no statistical significance between L-GrAFT 7 and EASE scores, which is consistent with the results reported in a German cohort by Moosburner et al . 25 The difference of the AUROCs in L-GrAFT 7 and L-GrAFT 10 was also small. However, only L-GrAFT can be calculated in the face of possible missing values, 26 and the missing values are mostly obtained between postoperative days 8–10 in clinical practice.…”
Section: Discussionmentioning
confidence: 94%